Injury scenarios of ankle sprains in the national football league: External rotation and eversion mechanisms - O`Cain, C. M.; Spratley, E. M.; Arbogast, K. B.; Lessley, D. J.; Evans, W. B.; Cormier, J. M.; Herzog, M. M.; Weir, N.; Crandall, J. R.; Coughlin, M. J.; Anderson, R. B. (The American Journal of Sports Medicine, 2025)
Background: Ankle sprains in American football resulting from external rotation and eversion (EE) mechanisms remain a persistent injury that often involves player-to-player contact. Currently, there is little research that describes the frequency or source of this contact in American football and what scenarios are responsible for these injuries across different player positions.